Pemetaan Pengembangan Potensi Vokasi Pesantrenpreneur (Studi Kasus di Pondok Pesantren Darussalam Dukuhwaluh Purwokerto) - Dewi Laela Hilyatin (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
In the perspective of human resource development, Islamic boarding schools today are no longer seen as religious institutions. More than that, Islamic boarding schools are considered capable of holding broader social and educational functions, namely the professional craters at the same time as Muslim converts. As many researchers have revealed, today most Islamic boarding schools have vocational specifications as institutional branding: cultural centers, language centers, community counseling centers, centers of creative economic development and others. Darussalam Pesantren as one of the developing boarding schools in Purwokerto has quite a lot of potential that has not yet been mapped and developed. This research is directed to focus on discussing the methodology of mapping potentials and developing potential vocational messages for pesantren Darussalam schools. From the research conducted it was concluded that the potential of Darussalam pesantren included: HR, facilities and infrastructure, the geographical location of the pesantren, the pesantren network and the legality of the pesantren. The mapping methodology includes: data collection, data presentation, data analysis and map usage. Vocational pesantrenpreneur that can be developed focus on economic and language development with three models, namely: Entrepreneurial Extracurricular, Student Internship and Industrial Maturity, Consolidation of Political Politics